Racial quotas at the university: a case study on access to Higher Education in a Federal Institution (Práxis Educativa, 2022)
In this text, the aim is to reflect on the implementation process of Law no. 12,711/2012, which provides for the admission into federal universities and federal institutions of secondary technical education, especially on the Pato Branco campus, at the Universidade Tecnológica Federal do Paraná (UTFPR). For this, we resorted to review, documentary analysis and academic production on the categories listed for this study: “Human Rights”, “Racial quota policy” and “Affirmative actions”, through a qualitative analysis. The results demonstrate that the effectiveness of the law ensured access to Higher Education courses, but not necessarily ensured the permanence of students in Higher Education. It is concluded that the full legal efficacy was not obtained, since only ensuring the access to Higher Education, without other guarantees for the dignified permanence of quota students, in the light of the data obtained, does not seem to be effective.Keywords: Affirmative actions. Quota Law. UTFPR.